KERATOCYSTIC ODONTOGENIC TUMOR OF THE MAXILLARY ANTERIOR REGION MASQUERADING AS A RADICULAR CYST - Satappa, Byakodi Sanjay; Vasant, Datar Uma; Kanitkar, Sampada; Kamat, Mamata (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Keratocystic odontogenic tumor (KCOT) is a benign odontogenic neoplasm which is characterized by aggressive behavior and a high recurrence rate. KCOTs have a predilection for the angle and ascending ramus of the mandible. Maxillary KCOTs are usually associated with nevoid basal cell carcinoma syndrome. Very few cases of non-syndromic KCOT crossing maxillary midline have been reported. In this article, we report a rare case of KCOT which presented as a multilocular radiolucency crossing midline and involving periapical area of maxillary incisors. The lesion thus simulated a periapical cyst. However, the lesion was proved to be a KCOT on histopathology. Thus this report highlights the need for histopathological evaluation of periapical lesions for accurate diagnosis and treatment plan.